2010
DOI: 10.1095/biolreprod.109.079095
|View full text |Cite
|
Sign up to set email alerts
|

Mice Deficient in the Serine/Threonine Protein Kinase VRK1 Are Infertile Due to a Progressive Loss of Spermatogonia1

Abstract: The VRK1 protein kinase has been implicated as a pro-proliferative factor. Genetic analyses of mutant alleles of the Drosophila and Caenorhabditis elegans VRK1 homologs have revealed phenotypes ranging from embryonic lethality to mitotic and meiotic defects with resultant sterility. Herein, we describe the first genetic analysis of murine VRK1. Two lines of mice containing distinct gene-trap integrations into the Vrk1 locus were established. Insertion into intron 12 (GT12) spared VRK1 function, enabling the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
57
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 45 publications
13
57
1
6
Order By: Relevance
“…Additional evidence implicating a role for VRK1 in germ cell development has also been demonstrated in the germline stem cells of Caenorhabditis elegans where a reduction in proliferation, but not an increase in apoptosis, causes the sterility defect observed in vrk-1 mutants (Gorjanacz et al, 2007;Waters et al, 2010). In mammals, VRK1 has been shown to affect germ cell proliferation in males, leading to sterility (Choi et al, 2010;Wiebe et al, 2010). Female mice lacking VRK1 function are reported to be sterile as well, but the basis for this phenotype is unknown.…”
Section: Introductionmentioning
confidence: 88%
“…Additional evidence implicating a role for VRK1 in germ cell development has also been demonstrated in the germline stem cells of Caenorhabditis elegans where a reduction in proliferation, but not an increase in apoptosis, causes the sterility defect observed in vrk-1 mutants (Gorjanacz et al, 2007;Waters et al, 2010). In mammals, VRK1 has been shown to affect germ cell proliferation in males, leading to sterility (Choi et al, 2010;Wiebe et al, 2010). Female mice lacking VRK1 function are reported to be sterile as well, but the basis for this phenotype is unknown.…”
Section: Introductionmentioning
confidence: 88%
“…In addition, VRK1 kinase activity is enhanced in response to DNA damage and is an early participant necessary for the formation of 53BP1 foci in response to DNA double-strand breaks induced by ionizing radiation, in both resting and dividing cells [31]. In murine gene-trap models, VRK1 deficiency results in sterility due to either meiotic defects in females or by affecting maintenance of spermatogonial stem cells prior to meiosis in males [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…The elimination of VRK1 in gene-trap mice has revealed that reduced levels of this kinase play an important role in meiosis, resulting in male and female sterility [47][48][49]. Also, the loss in mice of coilin, a phosphorylation target of VRK1 [50], is manifested by a sterility phenotype [51].…”
Section: Discussionmentioning
confidence: 99%